The Personality and Struggle of Bâdîs b. Habbûs, the Leader of the Zirid Dynasty in Al-Andalus - Erbil, Kadir (Fırat University, 2024)
In the history of Al-Andalus, Bâdîs b. Habbûs emerges as an influential leader, shining prominently in the mid-11th century as the ruler of the Al-Andalus Zîrî State. Bâdîs, belonging to the Berber Sanhâce tribe, attained a significant position in the political arena through remarkable ascent and leadership skills, establishing himself as a crucial figure in the Al-Andalus region. Throughout history, Sanhâce has been engaged in continuous rivalry with the Zenâte tribe, and the most notable period of these interactions occurred during the IV-VI (X-XII) centuries. In this crucial era, a Zenâte branch known as the Telkâtels established influential states in Ifrîkıye, the eastern part of Algeria, and Al-Andalus, drawing attention to their accomplishments. On the other hand, the Lemtûne and Messûfel tribes formed their independent states in Mağrib-i Aksâ, Al-Andalus, and the Balearic Islands. Telkâte, a prominent tribe affiliated with Sanhâce, settled in the Kosantîne province of Algeria during the 10th century. The leadership of Bâdîs, representing a critical period in the history of the Al-Andalus Zîrî State, commenced during the reign of II. Hakem with the aim of strengthening the Zîrî State and ensuring stability. Following the death of II. Hakem, Bâdîs was appointed to rectify the weakened state of the Zîrî State. In this critical period, Bâdîs's political acumen and leadership skills played a crucial role in stabilizing and expanding the state. Under his leadership, the Al-Andalus Zîrî State not only achieved political stability but also distinguished itself with cultural and intellectual advancements. Emir Bâdîs, by supporting local administrators in various regions of Al-Andalus, maintained regional balance and expanded the borders of the Zîrî State. Significant progress in science, literature, architecture, and the arts contributed to the cultural richness of Al-Andalus during his leadership. Bâdîs's effective leadership not only marked a significant era in the history of the Al-Andalus Zîrî State but also left a long-lasting legacy, influencing political and cultural developments in the region. After the death of Habbûs b. Mâksen in 429/1038, his son Bâdîs b. Habbûs ascended to the throne as the ruler of Granada. However, some Jews and Berbers demanded the accession of his brother Bulukkîn to the throne. Alongside these requests, a group that included Arabs and the vizier Samuel b. Nagrîle supported Bâdîs's rule. Under the leadership of Bâdîs b. Habbûs, the Zîrî Emirate experienced its most powerful period in Al-Andalus between 429-465 (1038-1073). During this time, the emirate emerged as one of the significant powers in the region. Bâdîs b. Habbûs's initial reign was shaped by various activities, including the education of his children, book critiques with scholars, receiving envoys, and a power struggle for the throne with his nephew Yiddîr b. Hubâse, who assumed the role of adviser. In the early years of his government, Emir Bâdîs made important decisions that contributed significantly to the strengthening of the emirate. This period is recorded as a time when the Zîrî Emirate held an influential position in the political scene of Al-Andalus, leaving a significant impact on the region. Bâdîs b. Habbûs was aware that the most significant obstacle to expanding his sovereignty was the Abbâdîs in Ishbiliya. The leader of the Abbâdîs was İsmâil, the son of Ebu’l-Kâsım b. Abbâd. Although Bâdîs b. Habbûs possessed a formidable military force, İsmâil, the leader of the Abbâdîs, aimed to eliminate the presence of Berbers in Al-Andalus. However, the greatest obstacle to this goal was Sultan Bâdîs b. Habbûs of Granada and his army. In an attempt to expand his dominance in Ishbiliya, Ebu’l-Kâsım Ibn Abbâd appointed his son İsmâil b. Abbâd as the hâcib. This strategic move was part of İbn Abbâd's strategy to enhance his influence beyond Ishbiliya. Nevertheless, faced with the risk to his material and especially spiritual authority, Yahyâ b. Ali b. Hammûd decided to unite Berber leaders to target Ishbiliya. During the Zîrî rule, disputes between Temîm b. Bulukkîn, the grandson of Bâdîs b. Habbûs, and his son Abdullah b. Bulukkîn persisted until the decline of the Zîrî dynasty.

Endülüs tarihinde, XI. yüzyılın ortalarında parlayan bir liderlik figürü olan Bâdîs b. Habbûs, Endülüs Zîrî Devleti’nin emiri olarak kayda geçmiş etkili bir liderdir. Berberî Sanhâce kabilesine mensup olan Bâdîs, siyasi arenada gösterdiği dikkate değer yükselişi ve liderlik becerileriyle Endülüs coğrafyasında önemli bir konum elde etmiştir. Sanhâce, tarih boyunca Zenâte boyu ile devamlı çekişme içinde bulunmuş ve bu etkileşimlerin en belirgin dönemini IV-VI. (X-XII.) yüzyıllar arasında deneyimlemiştir. Bu önemli dönemde, Telkâteler adlı bir Zenâte kolu, İfrîkıye, Cezayir'in doğu kısmı ve Endülüs'te etkileyici devletler kurarak dikkat çekmiştir. Lemtûne ve Messûfeler ise Mağrib-i Aksâ, Endülüs ve Balear Adaları’nda kendi bağımsız devlet yapılarını oluşturmuşlardır. Telkâte, Sanhâce'ye ait önemli kabilelerden biri olarak öne çıkmış ve X. yüzyılda Cezayir'in Kosantîne eyaletinde yerleşik bir hayat sürmekteydi. Endülüs Zîrî Devleti’nin tarihi boyunca kritik bir dönemi temsil eden Bâdîs’in liderliği, Zîrîler Devleti’nin güçlenmesi ve istikrarın sağlanması amacıyla II. Hakem’in hükümdarlığı sırasında başlamıştır. Bâdîs, II. Hakem’in ölümü sonrasında Zîrîler Devleti'nin zayıf durumunu düzeltmek üzere göreve getirilmiştir. Bu kritik dönemde, Bâdîs'in siyasi ustalığı ve liderlik yetenekleri, devletin istikrarını sağlama ve genişleme çabalarında önemli bir rol oynamıştır. Liderliği altında Endülüs Zîrîleri Devleti, sadece siyasi stabilite ile değil, aynı zamanda kültürel ve entelektüel gelişmelerle de ön plana çıkmıştır. Emir Bâdîs, Endülüs’ün çeşitli bölgelerindeki yerel yöneticilere verdiği destekle bölgesel dengeyi korumuş ve böylece Zîrîler Devleti’nin sınırlarını genişletmiştir. Bilim, edebiyat, mimari ve sanat alanlarında büyük ilerlemeler kaydedilmiş, bu da Endülüs’ü kültürel açıdan zenginleştirmiştir. Bâdîs’in etkili liderliği, Endülüs Zîrî Devleti’nin tarihinde önemli bir dönemi işaret etmekle kalmamış, aynı zamanda bölgedeki siyasi ve kültürel gelişmeleri etkileyerek uzun vadeli bir miras bırakmıştır. Habbûs b. Mâksen'in 429/1038 yılındaki ölümünün ardından, oğlu Bâdîs b. Habbûs Gırnata’nın hükümdarı olarak tahta geçmiştir. Ancak, Bazı Yahudiler ve Berberîler, kardeşi Bulukkîn’in tahta geçmesini talep etmişlerdir. Bu taleplerin yanı sıra, Araplar ve veziri Samuel b. Nagrîle’nin de dâhil olduğu bir grup, Bâdîs’in hükümdar olmasını desteklemiştir. Bâdîs b. Habbûs’un liderliğindeki Zîrîler Emirliği, 429-465 (1038-1073) yılları arasında Endülüs’teki en güçlü dönemini yaşamıştır. Emirlik, bu süre zarfında bölgenin önemli güçlerinden biri haline gelmiştir. Bâdîs b. Habbûs’un ilk hükümdarlık dönemi, çocuklarının eğitimi, fakihlerle kitap kritiği gerçekleştirme, elçileri karşılama ve danışmanlığını üstlenen kardeşinin oğlu Yiddîr b. Hubâse ile taht mücadelesi gibi çeşitli faaliyetlerle şekillenmiştir. Emir Bâdîs, hükümetinin ilk yıllarında önemli kararlar alarak emirliğin güçlenmesine önemli katkılarda bulunmuştur. Bu dönem, Endülüs siyasi sahnesinde Zîrîler Emirliği'nin etkileyici bir konum elde ettiği ve yönetiminin bölge üzerinde önemli bir etki bıraktığı bir dönem olarak kaydedilir. Bâdîs b. Habbûs, egemenlik alanını genişletme hedefiyle karşı karşıya olduğu en önemli engelin, İşbîliye'de bulunan Abbâdîler olduğunun farkındaydı. Abbâdîlerin lideri ise Ebu’l-Kâsım b. Abbâd'ın oğlu İsmâil'di. Bâdîs b. Habbûs, büyük bir askeri güce sahipti. Ancak, Abbâdî lideri İsmail, Endülüs'te varlığını sürdüren Berberîleri ortadan kaldırmak istiyordu, ancak bu hedefine en büyük engel, Gırnata sultanı Bâdîs b. Habbûs ve liderliğindeki ordusuydu. Ebü’l-Kâsım İbn Abbâd, İşbîliye'deki hâkimiyetini genişletmek amacıyla oğlu İsmâil b. Abbâd’ı hâcib olarak atadı. Bu stratejik hamle, İbn Abbâd’ın İşbîliye dışındaki etkisini artırma stratejisinin bir parçasıydı. Ancak, bu kararın ardından maddî gücü ve özellikle mânevî hâkimiyeti tehlikeye gelen Yahyâ b. Ali b. Hammûd, İşbîliye’yi hedef alarak Berberî liderlerini bir araya getirmeye karar verdi. Zîrî hükümdarlık döneminde, Bâdîs b. Habbûs’un torunu Temîm b. Bulukkîn ile oğlu Abdullah b. Bulukkîn arasında meydana gelen anlaşmazlıklar, Zîrî hanedanının gerilemesine kadar sürmüştür.
Endülüs Zîrîlerinin Lideri Bâdîs b. Habbûs Kişiliği ve Mücadelesi
Keywords: History of Islam; İslam Tarihi